Comparative Efficacy of Cryotherapy Versus Topical Trichloroacetic Acid 90% in Treatment of Common Warts - Gul, Kiran; Muzaffar, Bushra; Siddiqui, Muhammad Adeel; Hussain, Majid; Ilyas, Sara; Farid, Huma (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of Cryotherapy using liquid Nitrogen versus Trichloroacetic acid 90% in treatment of common warts.Study Design: Randomized Control Trial (ClinicalTrials.gov: NCT05712811).Place and Duration of Study: Department of Dermatology, Combined Military Hospital Abbottabad, Pakistan from Jun to Nov 2022.Methodology: Sixty patients with common warts (hard lesions, raised lumps with rough surfaces at the back of fingers, around nails and palm of hands) diagnosed by consultant dermatologist on clinical presentation were included in this study. The sample size was calculated by WHO Sample Size calculator. After randomization, patients were divided into two groups. Group-A was managed with Cryotherapy using liquid Nitrogen and Group-B was managed with topical Trichloroacetic acid 90%. Clinical evaluation was done at the end of twelfth week and then three months after the end of therapy to ascertain efficacy. Efficacy was established in terms of absence of all lesions with no recurrence/reappearance in both groups.Results: Cryotherapy using liquid nitrogen was more efficacious (83.3%) in terms of absence of all lesions with no recurrence/reappearance of warts as compared to 90.0% topical Trichloroacetic acid (60.0%) (p-value 0.045).Conclusion: This randomized controlled trial showed that Cryotherapy using liquid nitrogen was significantly more efficacious in treating common warts as compared to topical Trichloroacetic acid 90%.